MỘT SỐ KẾT QUẢ NGHIÊN CỨU PHÂN BỐ SÒ, ĐIỆP KHU VỰC NGHỆ AN - Triều, Cao Đình; Duẩn, Nguyễn Bá; Hải, Đặng Thanh; Thắng, Ngô Gia; Nam, Bùi Anh; Nguyên, Nguyễn Đình (Vietnam Journal of Earth Sciences, 2011)
Some results of placura and granosa shells distribution in Nghe An region On the basis of placura placenta-arca granosa shells investigation in Quynh Van, Dien Chau and Nghi Tien, some new results can be made as the following: - Banks of placura placenta-arca granosa shells in Quynh Van and Nghi Tien; deep-seated in Quynh Nghia, Dien Chau and along Nghi Yen seashore have the time of 4000-4600 yr. - The appearance of the placura placenta-arca granosa shells banks have not either the sources from marine transgression in Holocene, tectonic movement or artificial. - It is possible that those are the deposits of the natural geological activities courses to the seashore in the time of 4000-4600 yr ago.